Biochemical indices as correlates of recent growth in juvenile green turtles (Chelonia mydas) - Roark, Alison M. (2009)
Nucleic acid and protein concentrations and their ratios are increasingly used as correlates of nutritional condition and growth in marine species. However, their application in studies of reptile growth has not yet been validated. The green turtle (Chelonia mydas) is an endangered marine reptile for which assessing population health requires knowledge of demographic parameters such as individual growth rates. The purpose of this study was to evaluate a number of biochemical indices ([DNA], [RNA], RNA:DNA ratio, [protein], protein:DNA ratio, and RNA:protein ratio) in liver, heart, and blood as potential predictors of recent growth rate in juvenile green turtles under controlled feeding conditions. Intake of juvenile green turtles was manipulated over twelve weeks to obtain a range of growth rates. With the exception of [RNA](blood), [DNA](heart), and [protein]:[DNA](liver), all biochemical indices demonstrated significant linear relationships with growth rate during the last 1.5 weeks of the study. The best single predictors of recent growth were hepatic [RNA] and [RNA]:[protein], which explained 66% and 49%, respectively, of the variance in growth. Contrary to expectations, these two indices were negatively correlated with growth rate. To investigate the possibility that hepatic [RNA] was higher in slow-growing turtles because of elevated expression of antioxidant genes, we quantified glutathione peroxidase activity and total antioxidant potential. Both measures of antioxidant function were affected by intake and growth histories, but these effects did not explain our results for hepatic RNA and protein concentrations. We developed a model that predicted 68% of the variance in specific growth rate (SGR) with the equation SGR = −0.913(ln[RNA](liver)) + 17.689(Condition Index) + 4.316. In addition, our findings that [DNA] and [RNA]:[DNA] for blood were significantly correlated with SGR demonstrate the potential utility of minimally invasive tissue sampling that could facilitate instantaneous population monitoring.